Macrophages in inflammatory skin diseases and skin tumors - Liu, Si-Han; Zhang, Jie; Zuo, Ya-Gang (Frontiers in Immunology, 2024)
Macrophages, as specialized, long-lasting phagocytic cells of the innate immune system, have garnered increasing attention due to their wide distribution and various functions. The skin, being the largest immune organ in the human body, presents an intriguing landscape for macrophage research, particularly regarding their roles in inflammatory skin diseases and skin tumors. In this review, we compile the latest research on macrophages in conditions such as atopic dermatitis, psoriasis, systemic sclerosis, systemic lupus erythematosus, rosacea, bullous pemphigoid, melanoma and cutaneous T-cell lymphoma. We aim to contribute to illustrating the pathogenesis and potential new therapies for inflammatory skin diseases and skin tumors from the perspective of macrophages.